The Use of Traditional Gundu Games in Improving Student Discipline in Mathematics - Kamid Kamid; Husni Sabil; Wardi Syafmen; Siti Rohana (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to determine the relationship and influence between the character of discipline and student responses in the traditional game of gundu (marbles) in mathematics. This research was conducted at SD IT Aulia, SD Islam Muntaz, and SDN 112/I Perumas, Batanghari district. The method in this study was comparative quantitative data analysis. Where comparative is research that compares two or more variables. The results of this study are descriptive statistical tests of the character of the traditional game of gundu (marbles) on student responses to the mathematics subject at SDN 112/I Perumas which has a very good percentage for the results of the discipline character as well as for the results of student responses to traditional games. Followed by the assumption test where the three schools on the normality test are normally distributed and the linearity test has a linear relationship. Then proceed with the correlation test has a relationship and the regression test has an effect. So it can be concluded that the character of discipline on student responses to traditional games is interconnected and influential